Retreatment with nivolumab for patients with recurrent and/or metastatic head and neck cancer. (1st February 2022) - Wakasugi, Tetsuro; Takeuchi, Shoko; Ohkubo, Jun-ichi; Suzuki, Hideaki
Abstract: Background: After treatment with an immune checkpoint inhibitor (ICI) is discontinued, retreatment with an ICI is a potential sequential treatment, but the clinical efficacy/safety data for this treatment of recurrent and/or metastatic head and neck cancer (R/M-HNC) are limited. Aims/Objectives: This study aimed to evaluate the efficacy and safety of retreatment with nivolumab in R/M HNC. Materials and Methods: We divided the 29 eligible R/M-HNC patients who discontinued ICI treatment at our hospital into two cohorts to analyze the clinical characteristics and the efficacy of the salvage therapy: the Niv cohort (nivolumab retreatment) and the no-Niv cohort (no nivolumab retreatment). Results: The Niv cohort's median overall survival (OS) of 17.5 months (95% confidence interval [CI]: 2.7–32.3) was significantly prolonged compared to that of the no-Niv cohort: 5.8 months (95%CI: 2.4–9.2, p = .034). The Niv cohort achieved objective response rate of 16.7% and a disease control rate of 50.0%. No adverse events > grade 3 occurred in the Niv cohort. Conclusion: Nivolumab retreatment is an option for sequential treatment post-immunotherapy.